Partnering with Patients and Families to Prevent Maternal Morbidity and Mortality. Issue 1 (January 2021) - Wisner, Kirsten
Abstract : Approximately 700 women die each year in the United States from pregnancy-related complications. American Indian/Alaska Native and Black women are disproportionately affected and are two to three times more likely to die than White women. Two-thirds of these deaths are likely preventable. Several organizations have developed campaigns to raise awareness about the urgent maternal warning signs; Association of Women's Health, Obstetric, and Neonatal Nurses, Centers for Disease Control and Prevention, and Council on Patient Safety in Women's Health Care. Our maternity nursing expert, Dr. Wisner, provides an overview.